Sul problema della rappresentazione della individualità nella tragedia - Garzya, Antonio (Cuadernos de Filología Clásica. Estudios griegos e indoeuropeos, 2005)
Contrary to the most common opinion, the representation of singular individuals, i.e. characters, has always been a hallmark of the Greek tragic poets: the surviving dramas offer splendid instances. In this paper the question is considered both synchronically and diachronically, and extends a debate that has taken place throughout the last century, developing from memorable attitudes (from Aristotle to Hegel, etc.) We try to avoid any romantic approach as well as any abstract, anti-individualistic schemes.